The transportation logistics in Supply Chain Management and RMG sector in Bangladesh - Shohag, Hasibuzzaman (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.